Comparative Analysis of Neural Networking and Regression Models for Time Series Forecasting - S. V. Sholtanyuk (Цифровая трансформация, 2019)
Applicability of neural nets in time series forecasting has been considered and researched. For this, training of neural network on various time series with preliminary selection of optimal hyperparameters has been performed. Comparative analysis of received neural networking forecasting model with linear regression has been performed. Conditions, affecting on accuracy and stability of results of the neural network, have been revealed.